Perubahan Aktivitas Self Management Pada Klien Penyakit Paru Obstruksi Kronik - Rima Berti Anggraini; Adi Fahrudin; Nyimas Heny P (Citra Delima Scientific journal of Citra Internasional Institute, 2019)
COPD is a group of lung diseases characterized by increased airway resistance that is caused by narrowing of the airway lumen down. Characteristics of COPD symptoms are dyspnea, cough, and excessive sputum production. Self management is a strategy that gives the client a chance COPD to regulate or monitor their own behavior associated with health status. The purpose of this study to obtain in-depth information about the client's experience of self-management in COPD. This study uses a qualitative research design with phenomenology approach. Informants were used in this study are 5 the male sex. This study was conducted at the General Hospital of Depati Hamzah Pangkalpinang Bangka Belitung. The research was conducted in April - June 2016. The results showed one themes, such as changes in activity that occurred. The suggestion for COPD patients are to be more comprehend about their disease and increase self management in their daily life.